Implementasi Multiliterasi Melalui Pendekatan Ekologi Sastra Dalam Pembelajaran Bahasa Indonesia Di Era Digital - Fadli, Bagus Muhamad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study examines the implementation of multiliteracy through an ecocritical approach in Indonesian language learning in the digital era. The research objective is to analyze the effectiveness of integrating multiliteracy and literary ecology to improve students' language competence and environmental awareness. The research method uses a qualitative approach with a classroom action research design conducted at MA Darul Hikmah Kabupaten Bima for three months. The research subjects were 32 students of class XI. Data collection techniques using observation, interviews, and document analysis. Research instruments in the form of observation sheets, interview guidelines, and multiliteracy assessment rubrics. The results showed that the implementation of multiliteracy through an ecocritical approach could increase: (1) students' digital literacy skills by 78%, (2) visual literacy skills by 82%, (3) critical literacy skills by 75%, and (4) ecological awareness by 85%. This approach also successfully integrates Indonesian language learning with contemporary environmental issues, creating meaningful and relevant learning. The research implications show the importance of transforming Indonesian language learning that integrates various types of literacy with ecological awareness to prepare students to face 21st century challenges.